Galvanic Vestibular Stimulation Improves Arm Position Sense in Spatial Neglect: A Sham-Stimulation-Controlled Study. (July 2013) - Schmidt, Lena; Keller, Ingo; Utz, Kathrin S.; Artinger, Frank; Stumpf, Oliver; Kerkhoff, Georg
Background . Disturbed arm position sense (APS) is a frequent and debilitating condition in patients with hemiparesis after stroke. Patients with neglect, in particular, show a significantly impaired contralesional APS. Currently, there is no treatment available for this disorder. Galvanic vestibular stimulation (GVS) may ameliorate neglect and extinction by activating the thalamocortical network. Objective . The present study aimed to investigate the immediate effects and aftereffects (AEs; 20 minutes) of subsensory, bipolar GVS ( M = 0.6 mA current intensity) on APS in stroke patients with versus without spatial neglect and matched healthy controls. Methods . A novel optoelectronic arm position device was developed, enabling the precise measurement of the horizontal APS of both arms. In all, 10 healthy controls, 7 patients with left-sided hemiparesis and left-spatial neglect, and 15 patients with left hemiparesis but without neglect were tested. Horizontal APS was measured separately for both forearms under 4 experimental conditions (baseline without GVS, left-cathodal/right-anodal GVS, right-cathodal/left-anodal GVS, sham GVS). The immediate effects during GVS and the AEs 20 minutes after termination of GVS were examined. Results . Patients with neglect showed an impaired contralateral APS in contrast to patients without neglect and healthy controls. Left-cathodal/right-anodal GVS improved left APS significantly, which further improved into the normal range 20 minutes poststimulation. GVS had no effect in patients without neglect but right-cathodal/left-anodal GVS worsened left APS in healthy participants significantly. Conclusions . GVS can significantly improve the impaired APS in neglect. Multisession GVS can be tested to induce enduring therapeutic effects.